Analisis Kualitas Pelayanan dan Persepsi Harga Terhadap Kepuasan Pelanggan Studi Pada PDAM Kabupaten Cirebon - Yudianto, Agus; Hidayat, Riskin (STIE YPPI Rembang, 2009)
Abstract This research is a case study on PDAM Cirebon regency. This study aims to examine the impact of service quality and price perceptions to customer satisfaction. The sam- pling technique in this study using convenience sampling and obtained a sample of 135 respondents. To measure the state- ment items used in this study the Likert scale, with a scale of 1-5. Item statement of the variable service quality is 22 items, price perception is 14 items, and customer satisfaction is 8 items. Results of validity testÂ using factor analysis showed that all indicators have a loading factor greater than 0.40 and only loading on one factor. Results of reliability test showed that each construct has a Cronbachâs alpha values that can be received that is above 0.60 as the minimum criteria to be acceptable. Results of hypothesis test indicate that hypoth- esis 1 and 2 supported, which means that the service quality and price perception has positive influence on customer sat- isfaction, with their respective significance at 1% and 5%.Keyword: Service quality, Price perception, Customer satis- faction